Subtitusi Tepung Komposit Talas - Kacang Hijau (Takau) pada Pembuatan Roll Cake - Ignatius Bagus Dewanata; Any Sutiadiningsih; Ila Huda Puspita Dewi; Sri Handajani (STIKes Ibnu Sina Ajibarang, 2024)
Roll cake is generally made from flour that gives structure, texture, and softness. The selection of the right flour also plays an important role in the final result roll cake. This study was conducted to modify the ingredients of roll cake is the ratio of Taro flour and green beans as a substitute for wheat. The purpose of this study was to determine the organoleptic properties of the finished roll cake. This research is an experiment. The data collection technique used was observation through 5 trained panelists and 25 semi-trained panelists assisted by observation sheets assessing the interval distance between the upper and lower values (5-1). Data analysis using a single Anava (Analysis of Variance) test. The test results showed the characteristics of rectangular shape, golden yellow color, fragrant aroma, texture and taste are distinctive and Sweet; has a nutritional content of carbohydrates 48.78%, 8.71% protein, fat 3.19%, 38.81% water and 0.16% ash. 1. Need to do the use of butter that has a quality brand, 2. Need to perform additional comparative test 60%: 40%, 3. Further research needs to be done to produce the best roll cake including the safe and innovative packaging for consumers, 4. Need to do endurance test and storage on the cake roll.